Nadine Gordimer’s late style: An analysis of selected stories from Loot and Beethoven Was One-Sixteenth Black - Pawlicki, Marek (Studia Anglica Posnaniensia, 2023)
Nadine Gordimer frequently emphasized that style is closely connected to subject matter, which, in her case, derived in large part from national and global politics. Her late short stories are only a partial testimony to this truth insofar as their style is shaped both by Gordimer’s political views and by her approach to deeply personal topics, including love, desire, loss, mourning, and death. While the literary criticism of Gordimer’s works tends to concentrate on the political dimension of her writing, the aim of this discussion is to explore late style in the context of personal topics recurrent in Gordimer’s late short fiction, especially the topics that have been mentioned above. The article begins with a brief discussion of Gordimer’s views on literary style and goes on to examine theoretical perspectives on the phenomenon of late style, including the works of Theodor Adorno, Edward Said, Linda and Michael Hutcheon, J.M. Coetzee, and Graham Riach. The main aim of the theoretical part of the article is to draw a clear distinction between Spätstil and Altersstil, and, in this way, to lay the foundation for the analysis of Altersstil (defined as a characteristic individual style that comes with advancing age) in Gordimer’s stories. The analytical part of the article, devoted equally to Gordimer’s late style and to the thematic preoccupations of her late short fiction, concentrates on six stories selected from Gordimer’s last two volumes: Loot and Other Stories (2003) and Beethoven Was One-Sixteenth Black and Other Stories (2007). In both these collections, Gordimer’s style is characterized by her experimentation with narrative perspectives, as well as the adoption of the autobiographical and confessional modes. Gordimer’s late writing is also distinguished by intertextuality, self-reflexivity, and its interest in the workings of memory.